Letters to India - Tolley Clive (Åbo Akademi, 2022)
I write as a non-Jew about the brief correspondence sent to my father, shortly after the Second World War, from a gifted, young Jewish violinist, and briefly outline the background story-arc of her family’s aliyah, from the Pale a couple of generations earlier to her settlement in the new state of Israel. Her story is not bound up with the Holocaust, nor (as far as we know) did she experience antisemitism: but this essay attempts to highlight the majesty and sparkle of a moment in the mundane life of a Jewish woman, and its brief impact on a gentile. The focus is on her musical remarks about some of the leading performers of the day. I also outline some of the ways I secured source materials for this primarily biographical sketch, but this article is presented more as a ‘memoire’ than an academic study. It is offered in honour and memory of a Jewish lady whom, alas, I was a little too late to meet myself, and to celebrate my father’s hundredth birthday in May 2021.